Evaluation of Quality Parameters of Light Sensitive Drugs Marketed in Nepal - Maharjan, Sajan; Dhungel, Subhash Kumar (Journal of Nepal Health Research Council, 2023)
Background: Photosensitivity is the response of drug or drug product to the exposure of solar, UV and visible light in the solid, semisolid, or liquid state that leads to a physical or chemical change. Exposure to light is a concern with numerous medications due to the potential for photo degradation or other chemical reactions that affect drug stability.Methods: Out of all the registered brands in Department of Drug Administration, 9 brands of Rabeprazole tablets, 5 brands of Promethazine tablets and 5 brands of methylcobalamin tablets were selected and were subjected for testing and analysis for various quality parameters as per pharmacopoeia. The labels of the collected medicine were analyzed. The obtained data were entered and analyzed in Microsoft office excel 2019.Results: Eleven products did not comply with the existing regulatory requirement on labeling system of medicine as per Regulation of Standard of drugs. There was no uniformity in mentioning the self-life. Similarly, large variation was seen on price of same generic drugs. Information regarding storage conditions, direction for use and category of the drug were lacking in the label of some brands of medicines.Upon Laboratory analysis, two brands of promethazine tablets and three brands of Rabeprazole tablets were found substandard. Drug content of all the brands of Methylcobalamin was found to contain overage.Conclusions: The result of this study indicates that substandard medicines are abundant in Nepalese market. There is weak regulation monitoring which have resulted in no uniformity in similar pharmaceutical products too. Hence, stringent regulatory monitoring is required to assessthe quality of pharmaceutical products in the Nepalese market.Keywords: Light sensitive drugs; substandard drugs; quality of drugs